Web-Based Return of Individual Patient-Reported Outcome Results Among Patients With Lymphoma: Randomized Controlled Trial - Simone Oerlemans; Lindy Paulina Johanna Arts; Jacobien M Kieffer; Judith Prins; Mels Hoogendoorn; Marjolein van der Poel; Ad Koster; Chantal Lensen; Wendy Bernadina Catharina Stevens; Djamila Issa; Johannes F M Pruijt; Margriet Oosterveld; et al. (JMIR Publications, 2021)
BackgroundThere has been a cultural shift toward patient engagement in health, with a growing demand from patients to access their results. ObjectiveThe Lymphoma Intervention (LIVE) trial is conducted to examine the impact of return of individual patient-reported outcome (PRO) results and a web-based self-management intervention on psychological distress, self-management, satisfaction with information, and health care use in a population-based setting. MethodsReturn of PRO results included comparison with age- and sex-matched peers and was built into the Patient-Reported Outcomes Following Initial Treatment and Long-Term Evaluation of Survivorship registry. The self-management intervention is an adaptation of a fully automated evidence-based intervention for breast cancer survivors. Patients with lymphoma who completed the web-based questionnaire were equally randomized to care as usual, return of PRO results, and return of PRO results plus self-management intervention. Patients completed questionnaires 9 to 18 months after diagnosis (T0; n=227), 4 months (T1; n=190), 12 months (T2; n=170), and 24 months (T3; n=98). ResultsOf all invited patients, 51.1% (456/892) responded and web-based participants (n=227) were randomly assigned to care as usual (n=76), return of PRO results (n=74), or return of PRO results and access to Living with lymphoma (n=77). Return of PRO results was viewed by 76.7% (115/150) of those with access. No statistically significant differences were observed for psychological distress, self-management, satisfaction with information provision, and health care use between patients who received PRO results and those who did not (P>.05). Use of the self-management intervention was low (2/76, 3%), and an effect could therefore not be determined. ConclusionsReturn of individual PRO results seems to meet patients' wishes but had no beneficial effects on patient outcome. No negative effects were found when individual PRO results were disclosed, and the return of individual PRO results can therefore be safely implemented in daily clinical practice. Trial RegistrationNetherlands Trial Register NTR5953; https://www.trialregister.nl/trial/5790 International Registered Report Identifier (IRRID)RR2-10.1186/s13063-017-1943-2